Competition law as a tool to ensure diversity of voices and access to the media - Shuaib, Farid Sufian (2009)
With two state-owned television stations, four commercial free-to-air television stations and about hundred channels to choose from paid broadcasters, the Malaysian public are spoiled for choices. However, the two state-owned television stations have constantly refused to give reasonable coverage for those outside the government – particularly the opposition – since the two is regarded as the official channel of the government of the day. Choices of the Malaysian public to receive information and opinions of public interest may in fact be limited because of the crude and transparent control of the media by the ruling parties. This paper seeks to explore Malaysian competition law clauses in Malaysia and legislation from other countries to facilitate the opening up of media ownership to ensure diversity in the media.